2016
DOI: 10.1262/jrd.2016-066
|View full text |Cite
|
Sign up to set email alerts
|

Superovulation with a single administration of FSH in aluminum hydroxide gel: a novel superovulation method for cattle

Abstract: Superovulation (SOV) is a necessary technique to produce large numbers of embryos for embryo transfer. In the conventional methods, follicular stimulating hormone (FSH) is administered to donor cattle twice daily for 3 to 4 days. As this method is labor intensive and stresses cattle, improving this method has been desired. We previously developed a novel and simple SOV method, in which the intramuscular injection of a single dose of FSH in aluminum hydroxide gel (AH-gel) induced the growth of multiple follicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
6

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 54 publications
0
11
0
6
Order By: Relevance
“…However, multiple injections of FSH are required due to its short half-life, which is time-consuming and may also be stressful for the cows (Sugano and Shinogi, 1999;Chasombat et al, 2013). Many previous studies proposed solving this issue by administering FSH dissolved in various agents that provide a slow release, such as polyvinylpyrrolidone (PVP) (Yamamoto et al, 1994;Takedomi et al, 1995;Ratsiri et al, 2021) and aluminium hydroxide gel (AH-gel) in cattle (Kimura, 2016). However, those diluting agents make the solution viscous and difficult to prepare well with FSH.…”
Section: Introductionmentioning
confidence: 99%
“…However, multiple injections of FSH are required due to its short half-life, which is time-consuming and may also be stressful for the cows (Sugano and Shinogi, 1999;Chasombat et al, 2013). Many previous studies proposed solving this issue by administering FSH dissolved in various agents that provide a slow release, such as polyvinylpyrrolidone (PVP) (Yamamoto et al, 1994;Takedomi et al, 1995;Ratsiri et al, 2021) and aluminium hydroxide gel (AH-gel) in cattle (Kimura, 2016). However, those diluting agents make the solution viscous and difficult to prepare well with FSH.…”
Section: Introductionmentioning
confidence: 99%
“…Despite satisfying results (a large number of corpora lutea and transferable embryos collected), PVP seemed to be an adjuvant with some defects. The FSH suspension in PVP characterized with high viscosity, which created some difficulties to achieve a homogeneous mixture and limited its practical application (6,23). However, as no other undesirable effects have been demonstrated, PVP is still used in some countries as an adjuvant in commercial FSH preparations (10).…”
Section: Conventional Methods Of Inducing Superovulation In Cattlementioning
confidence: 99%
“…It was shown that for cattle receiving single intramuscular doses of 30 mg of pFSH with 5 ml of aluminum hydroxide gel, the number of corpora lutea, the total number of ova and the number of transferable embryos collected did not differ significantly from the conventional pFSH treatment. However, the disadvantage of AH-gel applied intramuscularly were pathological changes in the site of administration in the form of granulomas and swelling accompanied by a significant accumulation of macrophages, monocytes and giant cells (23). These pathological changes at the place of injection in meat cattle caused significant economic losses and growing consumer dissatisfaction.…”
Section: Conventional Methods Of Inducing Superovulation In Cattlementioning
confidence: 99%
See 1 more Smart Citation
“…Although some people feel that large offspring syndrome may be relegated Current donor follicle stimulation protocols require multiple daily injections due to the relative short half-life FSH preparation in the female blood circulation. Current strategies to overcome this labour-intensive situation are based on using long-acting FSH analogs through a slow release formulation (Kimura, 2016), or even more desirable, replacing pituitary-derived preparations with recombinant bovine FSH (Carvalho et al, 2014). Promising research developments in the near future will likely be associated with bovine recombinant FSH for donor stimulation (Hesser, Morris, & Gibbons, 2011).…”
Section: Con Clus Ionsmentioning
confidence: 99%